Granuloma faciale: a rare disease from a dermoscopy perspective - Danilo Augusto Teixeira; Bruna Estrozi; Mayra Ianhez (Sociedade Brasileira de Dermatologia, 2013)
The granuloma faciale is a rare and benign skin disease of unknown etiology, characterized by chronic leukocitoclastic vasculitis. It is characterized by skin lesions predominantly facial whose course is chronic and slowly progressive. The diagnosis is based on clinical features, histopathology and, more recently, in dermoscopy. We describe the case of a male patient, 40 years old, with a sarcoid lesion on the malar site, whose histopathological examination revealed a mixed inflammatory infiltrate with presence of Grenz zone. Dermoscopy revealed a pink background with white striations. The definitive diagnosis is made by histopathologic evaluation, and dermatoscopy can be helpful. It is known to be resistant to therapy, oral medications, intralesional and surgical procedures are options.